2022
DOI: 10.1177/19417381211065768
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Use of Player Load in Elite Soccer Players

Abstract: Background: The aims of this study were to (1) analyze the distribution of the player load (PLTOTAL) in 3 axes of movement (PLAP, anterior-posterior; PLML, medial-lateral; PLV, vertical) during elite soccer matches, (2) investigate the effect of playing position on PL-related variables, and (3) explore the association between PLTOTAL and distance covered by the players. Hypothesis: Despite different load distribution between axes of movement, PLTOTAL might be used as a body load indicator for all playing posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…When the match finished, the same research team member transferred the data to SPro software (RealTrack Systems, Almería, Spain) through a Smart Station (RealTrack Systems). This software generated the "Intervals Pro report, which contained the following load measures: total of steps (count), distance covered (m), explosive distance (m, above 1.12 m•s 22 ), power metabolic (W•kg 21 ), player load (a.u), impacts (count), accelerations (count), decelerations (count), and the FFT duration (minutes) (21,27). Specifically, the FFT duration is defined as the total time in which the intensity of the FFT (i.e., a mathematic calculation that is used to convert signals from original domains such as time or space to frequency domains) is applied to the total acceleration data, which were recorded by the triaxial accelerometers (i.e., ACELT), is above 0.02.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the match finished, the same research team member transferred the data to SPro software (RealTrack Systems, Almería, Spain) through a Smart Station (RealTrack Systems). This software generated the "Intervals Pro report, which contained the following load measures: total of steps (count), distance covered (m), explosive distance (m, above 1.12 m•s 22 ), power metabolic (W•kg 21 ), player load (a.u), impacts (count), accelerations (count), decelerations (count), and the FFT duration (minutes) (21,27). Specifically, the FFT duration is defined as the total time in which the intensity of the FFT (i.e., a mathematic calculation that is used to convert signals from original domains such as time or space to frequency domains) is applied to the total acceleration data, which were recorded by the triaxial accelerometers (i.e., ACELT), is above 0.02.…”
Section: Methodsmentioning
confidence: 99%
“…The positioning systems provide important performance variables such as distance covered, maximum speed, and total accelerations or decelerations (29). In this regard, inertial sensors allow a 3dimensional analysis, whereas positioning-based tracking systems provide variables that are a representative of a 2dimensional analysis (e.g., distance covered) (22). Therefore, one of the main advantages of inertial sensors is that they allow further analysis of sport-specific movements such as changes of direction, jumps, impacts, body load, or landings (5,29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of nine elite RH players, there were no significant differences throughout all observed metrics during a competition between players' positions (57). Furthermore, variable load distribution (total PL) based on the axis of movement was not verified based on playing position (58). However, total PL appears suitable for monitoring locomotor demands or accelerometer-derived load in FTB (58).…”
Section: Applicability Of the Tracking System Related To Performance ...mentioning
confidence: 98%
“…Furthermore, variable load distribution (total PL) based on the axis of movement was not verified based on playing position (58). However, total PL appears suitable for monitoring locomotor demands or accelerometer-derived load in FTB (58).…”
Section: Applicability Of the Tracking System Related To Performance ...mentioning
confidence: 98%